Nanotechnology : consequences for human health and the environment - Hester, R. E.; Harrison, Roy M., 1948- (Royal Society of Chemistry, 2007)
This product is not available separately, it is only sold as part of a set. There are 750 products in the set and these are all sold as one entity. This product is not available separately, it is only sold as part of a set. There are 750 products in the set and these are all sold as one entity.
Keywords: Nanotechnology -- Health aspects.; Nanotechnology -- Environmental aspects.; Risk assessment.; elektronické knihy; electronic books